1998
DOI: 10.1097/00005344-199807000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of α1-Adrenergic Receptor mRNA Species in Rat Heart

Abstract: Radioligand binding studies have detected alpha1A- and alpha1B-adrenergic receptors (AR) in rat heart, but the ligands available for these studies lack the sensitivity and specificity needed to map possible differences in alpha1-AR subtype expression. We therefore used competitive reverse transcriptase-polymerase chain reaction (RT-PCR) techniques to measure steady-state amounts of alpha1-AR messenger RNA (mRNA) subtypes in tissue dissected from several regions of rat heart. We detected mRNA for alpha1A-, alph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 17 publications
1
11
0
1
Order By: Relevance
“…In general, our data also agree with those of Wolff et al (1998) about the distribution of α 1 -adrenoceptor mRNA in different parts of the heart although we do not find the differences in the distribution of α 1A -adrenoceptor mRNA. Moreover, we were able to identify not only the differences in the distribution of mRNA, but also in the density of binding sites for α 1B -adrenergic receptors.…”
Section: Discussionsupporting
confidence: 91%
“…In general, our data also agree with those of Wolff et al (1998) about the distribution of α 1 -adrenoceptor mRNA in different parts of the heart although we do not find the differences in the distribution of α 1A -adrenoceptor mRNA. Moreover, we were able to identify not only the differences in the distribution of mRNA, but also in the density of binding sites for α 1B -adrenergic receptors.…”
Section: Discussionsupporting
confidence: 91%
“…After Langendorff perfusion for 3-4 min at 37°C with Ca 2ϩ -free Tyrode solution containing 0.2 mg/ml collagenase (Nitta Zerachin, Tokyo, Japan) and 0.04 mg/ml protease (type XIV, Sigma Chemical, St. Louis, MO, USA), the enzymes were washed out with 0.2 mM Ca 2ϩ -Tyrode solution, and cells were dispersed from the ventricular tissue into a dish. We obtained myocytes from the left ventricle or septum, because ␣ 1 -adrenoceptor could be localized in the left ventricle or septum [12]. The isolated cells were stored in 1 mM Ca 2ϩ -Tyrode solution at 4°C until use (up to 8 h).…”
Section: Methodsmentioning
confidence: 99%
“…While there seems to be agreement in the literature that in neonatal rat cardiomyocytes α 1 -AR-stimulated cardiac hypertrophy is brought about by α 1A -AR stimulation (Knowlton et al 1993;Autelitano and Woodcock 1998;Rohde et al 2000), it is not known which α 1 -AR subtype might mediate α 1 -ARevoked hypertrophic response in adult rat ventricular cardiomyocytes. In the adult rat heart (Price et al 1994;Scofield et al 1995;Wolff et al 1998) and in adult rat cardiomyocytes (Rokosh et al 1996) at the mRNA-level all three α 1 -AR subtypes have been demonstrated with α 1B -AR having the greatest abundance (Price et al 1994;Wolff et al 1998). Similarly, binding studies in the rat heart have revealed an α 1A :α 1B -AR ratio of 20%:80% (Michel et al 1994a) while it is still a matter of debate whether or not α 1D -AR can be demonstrated in the rat heart on a protein level (Deng et al 1996;Yang et al 1997).…”
Section: Introductionmentioning
confidence: 99%